Strafen mit neuer Begründung - Teuchert, Lisanne (Zeitschrift für evangelische Ethik, 2021)
Mostly, theological ethics still refers to classical theories in dealing with criminal law and punishment. These are retributivism and prevention theories in their various versions or their combination in a mixed theory. However, new approaches in legal philosophy have emerged. Four of them are presented in this paper: the expressive-communicative approach, the victim-oriented approach, the fairness theory (unfair benefits), and the empirical-sociological approach. The strengths and weaknesses of each are analyzed. Finally, general tendencies are derived from the four theories and considered from a protestant ethical standpoint.
CRIS-Team Scopus Importer:2024-09-30
Keywords: Systematische Theologie; Dogmatik; Straftheorien; Rechtsphilosophie